Water, sanitation, and hygiene (WASH) coverage and practices of children from five public primary schools in Guinea - Alseny Bah; Alhassane 1 Diallo; Alhassane Bah; Feihu Li (Journal of Water, Sanitation and Hygiene for Development, 2022)
The water, sanitation, and hygiene (WASH) coverage and practices in and out of primary schools are crucial to the well-being of children. Using a questionnaire analysis method, this study focuses on the WASH coverage and practices of children from five public primary schools in the city of N'Zerekore, the second-largest city in Guinea. Our results reveal that the WASH coverage and practices in all five schools are inadequate. Our data indicated that 100% (n=1,048) of pupils don't wash their hands with soap after defecation in school, and over 87.9% (n=922) of students do not wash their hands before eating. The poor WASH coverage, inadequate hygiene practices, and other activities and/or causes result in a higher incidence of diseases among children, such as malaria, typhoid, and diarrhea. Some effective interventions, including the provision of clean water, sanitation and hygiene infrastructure, and widespread and effective health education, should be implemented to address these health issues among young African students. HIGHLIGHTS The current study highlights the WASH coverage and practices of children in Guinea.; WASH interventions such as access to an improved water source and improved water quality are urgently needed.;